(untitled) (Argos, 2025)
The Odyssey constitutes a catalog of monstrous beings, that break and transgress natural and social categories. The rupture of cultural codes (food, drink, sexuality, body and language) enables us to reconstruct the Greek experience of the monstrosity, considered as a cultural speech of the archaic era, and its function: to question and enhance certain values. Odysseus explores the marginal space of the Greek world in an effort of symbolic apropiation. His story makes the monsters carry out the work of warning and control, fulfilling the objectives of the creation of these creatures in Greek culture.